Annual Report for The Rowan Tree Church 1990-1991 - Rowan Tree Church (Northridge, CA: Rowan Tree Church, 1991, 1991)
The ninth Annual Report goes into detail how the Church can function as a community of groups, which are scattered throughout the United States and Canada. Rituals are synchronized so that all may participate. This is the first year the Annual Report is issued from Northridge, California.
This digital asset was created from the original digital scans by Rev. Paul V. Beyerl and provided to the Valdosta State University, Archives & Special Collections to be part of their Rowan Tree Church Periodicals Collection of the New Age Movements, Occultism, and Spiritualism Research Library. The Rowan Tree Church is an earth-based religion founded by Rev. Paul Beyerl, a Third Degree Initiate in the Alexandrian Tradition of Wicca, and incorporated on February 4, 1980 in Minneapolis, Minnesota. The church is now based in Kirkland, Washington with many communities throughout the United States and Canada. The roots of the Church extend back to 1976 which Rev. Beyerl began teaching Wicca, Astrology, and Herbalism out of his home. The Church's religion, The Tradition of Lothloriën, embraces inclusiveness and accepts all people regardless of faith, sexual orientation, race, or gender, a noted departure from early Alexandrian Wicca. The Tradition has elements of Herbalism, Astrology and Tibetan Buddhism in its structure, and is deeply rooted in its Mystery School, an in-depth study program that leads to Ordination, and the Hermit's Grove, its educational and publishing entity. Noted publications are The Unicorn, The Littlest Unicorn for children, and The Hermit’s Lantern.
Keywords: Rowan Tree Church--History; Lothloriën (Wiccan sect); Mystery School of Lothloriën; Wicca--Study and teaching; Littlest Unicorn (Rowan Tree Church); Galadhrim Society; Annual reports